The Lack of Attention to Lactation Needs in Media Companies - Widia Primastika; Afwan Purwanto Muin; Marina Nasution (Yayasan Jurnal Perempuan, 2021)
The fulfillment of exclusive breastfeeding is important not only for the babies and toddlers, but also for prevention of breast cancer to mothers and/ or women. Although the government has developed policies related to exclusive breastfeeding, the achievements are still inadequate. One of the problems is the lack of support from the workplace environment. This study focuses on the attention and support of media companies to the lactation needs of breastfeeding women journalists. This qualitative study uses the in-depth interview method and literature study. The results of the study show that media support for the lactation needs of female journalists is still very low. The newsroom must have a special policy that fully supports the lactation needs of journalists both at the office and outside the office. The study also found that full support from the social work environment plays a very important role in the success of a female journalist in giving exclusive breastfeeding.